UPM produces Milagro Matado to control pests in agricultural areas - Mohd Azhari, Nurul Ezzaty (Pusat Strategi dan Perhubungan Korporat, Universiti Putra Malaysia, 2023)
SERDANG, Dec 22 – Universiti Putra Malaysia (UPM) has successfully produced an organic plant pest insecticide known as Milagro Matado as an alternative to chemical pesticides in agricultural areas.